Isoprene Suppression by CO2 Is Not Due to Triose Phosphate Utilization (TPU) Limitation - Lantz, Alexandra T.; Solomon, Christine; Gog, Linus; McClain, Alan M.; Weraduwage, Sarathi M.; Cruz, Jeffrey A.; Sharkey, Thomas D. (Frontiers in Forests and Global Change, 2019)
Isoprene is one of the most abundant volatile organic compounds produced by some, though not all, plant species. It confers stress tolerance in both emitting and non-emitting species and has large impacts on gene regulation as well as on atmospheric chemistry. Understanding the control of isoprene emission from plants is important to understanding plant responses to future atmospheric conditions. In this study we determined that suppression of isoprene emission from plants by high CO2 concentrations is reduced but not eliminated by high temperature. We tested whether the CO2 suppression is caused by the reduction in ATP or NADPH availability caused by triose phosphate utilization (TPU) limitation of photosynthesis at high CO2. We measured CO2 assimilation as well as several photosynthetic electron transport parameters under multiple atmospheric conditions in four plant species grown at ambient CO2. While CO2 sensitivity of isoprene emission was somewhat correlated with TPU in some species, in other species it was not. Poplar exhibited significant CO2 suppression of isoprene emission but no evidence for TPU so we investigated further measuring the electrochromic shift that gives information on ATP synthesis and photosystem I oxidation state. In all cases photosynthetic parameters were unchanged while isoprene emission dropped in response to increasing CO2. Non-photorespiratory conditions (2% O2) led to an increase in isoprene emission at low CO2 but did not alleviate suppression by CO2. In all measured species the combination of higher temperature along with higher CO2 concentrations led to a net increase of isoprene emission in response to a moderate scenario for temperature and CO2 concentration in 2100 in the upper Midwest.